Pattern of sedentary behavior in brazilian adolescents - Ramos, Drielly Elvira (2018)
The present study objectively measured the pattern of sedentary behavior among schoolchildren from a city in southern Brazil. A probabilistic sample composed of 394 adolescents was selected from ten public schools in the city of Londrina/PR. The cut-point of 720 counts.min-1 for the vector magnitude from the ActiGraph accelerometer was used to estimate the total sedentary time, bouts (1-4 min, 5-9 min, 10-14 min, 15-29 min, and ≥ 30 min), and breaks during the week, on weekdays and at weekends, as well as at school and out of school. Adolescents spent about 10 hours per day in sedentary behavior. Total sedentary time in bouts was 50% (278 from 535 minutes) in short bouts. Adolescents demonstrated greater time in shorter bouts (< 10 minutes) within the school period and longer time in extended bouts (≥ 15 minutes) outside school (p < 0.05). Sex and socioeconomic status had no effect on sedentary time regarding bouts and number of breaks. Thus, Brazilian adolescents present high levels of sedentary time, especially during time outside school.